In Silico Prediction of Isoliquiritigenin and Oxyresveratrol Compounds to BCL-2 dan VEGF-2 Receptors - Mutiah, Roihatul; Hariz, Muhammad Fawaz; Indrawijaya, Yen Yen Ari; Ma'arif, Burhan (Indonesian Journal of Cancer Chemoprevention, 2019)
Isoliquiritigenin and oxyresveratrol are compounds that have been reported to have anticancer activities. This study aimed to predict cytotoxic activity, toxicity and physicochemical properties of the compounds isoliquiritigenin and oxyresveratrol. Prediction of physicochemical properties referred to Lipinski rules of five using the pkCSM online tool. Prediction of compounds toxicity using Protox II online tool while ligand interaction with receptors using Molegro Virtual Docker (MVD). Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) (PDB: 2RL5) and B Cell Lymphoma BCL-2 (PDB: 4AQ3) were used as target cancer receptor proteins. In silico predictive results showed that oxyresveratrol and isoliquiritigenin complied with Lipinski rules of five, predictive values of LD50 between 500-2000 mg/kg respectively 1560 mg/kg and 1048 mg/kg. The docking result was in the form of bound energy described by Rerank Score (RS). A compound having a small RS value was predicted to have greater activity. RS of oxyresveratrol on 2RL5: -73.0413 and 4AQ3: -87.9985, while isoliquiritigenin on 2RL5: -68.0282 and 4AQ3: -78.5041. The cytotoxic activity of oxyresveratrol was also shown by hydrogen bonds in active amino acids (2RL5: Cys 919 in 4AQ3: Tyr 67). From docking results of both compounds, oxyreveratrol had greater activity than isoliquiritigenin to both target cancer receptor proteins and complied Lipinski rules of five and have a low toxicity.Keywords: cytotoxicity, toxicity, isoliquiritigenin, oxyresveratrol, in silico.